SUBSTITUSI SORGUM DAN UBI JALAR PUTIH PADA ROTI BAGEL SEBAGAI ALTERNATIF SELINGAN UNTUK PENDERITA DIABETES[Substitution of Sorghum and White Sweet Potato on Bagels an Alternative Snack for Diabetics] - Vina Nur Ashfiyah (Universitas Airlangga, 2019)
Bread is a favorite food for Indonesian people as an alternative snack or breakfast. Bagel is one of breads that gain popularity in Indonesia. Sorghum and white sweet potato as local staple foods could be used as substitute ingredients for decreasing the consumption of wheat flour and made a low glycemic index snacks that suitable for diabetics. The aim of this research was to analyze the effect of sorghum and white sweet potato substitution toward acceptability (color, aroma, taste, and texture), nutrient value (energy, carbohydrate, fat, protein, fiber) and the glycemic index of bagel. This research was an experimental study with Completely Randomized Design with 8 repetitions. There were one control formula (F0) and two substitute formulas, F1 (substitution with white sweet potato 20%), and F2 (substitution with white sweet potato 20% and sorgum 10%). The untrained panelists were 30 diabetics. The difference test was analyzed by Kruskall Wallis dan Mann Whitney with confidence level 95% (α≤0.05). The result showed that the most favorite formula was F1 and there were no significant differences among the formulas in color (p=0.360), aroma (p=0.940), taste (p=0.160), and texture (p=0.120). The nutrient value of F1 can fulfilled the nutritional requirement of diabetics snacks which contain, energy 85%, carbohydrate 99%, fat 40%, protein 92%, and fiber 260%. It also have low glycemic index (54.6), so it can be and alternative snack for diabetics.